Line 1,622: |
Line 1,622: |
| ===Computation Summary for Logical Equality=== | | ===Computation Summary for Logical Equality=== |
| | | |
− | Figure 2.1 shows the expansion of <math>g = \texttt{((u, v))}</math> over <math>[u, v]\!</math> to produce the expression: | + | Figure 2.1 shows the expansion of <math>g = \texttt{((} u \texttt{,~} v \texttt{))}\!</math> over <math>[u, v]\!</math> to produce the expression: |
| | | |
| {| align="center" cellpadding="8" width="90%" | | {| align="center" cellpadding="8" width="90%" |
− | | <math>\texttt{uv} ~+~ \texttt{(u)(v)}</math> | + | | |
| + | <math>\begin{matrix} |
| + | uv & + & \texttt{(} u \texttt{)(} v \texttt{)} |
| + | \end{matrix}</math> |
| |} | | |} |
| | | |
− | Figure 2.2 shows the expansion of <math>\mathrm{E}g = \texttt{((u + du, v + dv))}</math> over <math>[u, v]\!</math> to produce the expression: | + | Figure 2.2 shows the expansion of <math>\mathrm{E}g = \texttt{((} u + \mathrm{d}u \texttt{,~} v + \mathrm{d}v \texttt{))}\!</math> over <math>[u, v]\!</math> to produce the expression: |
| | | |
− | {| align="center" cellpadding="8" width="90%" | + | {| align="center" cellpadding="8" width="90%" |
− | | <math>\texttt{uv} \cdot \texttt{((du, dv))} + \texttt{u(v)} \cdot \texttt{(du, dv)} + \texttt{(u)v} \cdot \texttt{(du, dv)} + \texttt{(u)(v)} \cdot \texttt{((du, dv))}</math> | + | | |
| + | <math>\begin{matrix} |
| + | uv \cdot \texttt{((} \mathrm{d}u \texttt{,~} \mathrm{d}v \texttt{))} & + & |
| + | u \texttt{(} v \texttt{)} \cdot \texttt{(} \mathrm{d}u \texttt{,~} \mathrm{d}v \texttt{)} & + & |
| + | \texttt{(} u \texttt{)} v \cdot \texttt{(} \mathrm{d}u \texttt{,~} \mathrm{d}v \texttt{)} & + & |
| + | \texttt{(} u \texttt{)(} v \texttt{)} \cdot \texttt{((} \mathrm{d}u \texttt{,~} \mathrm{d}v \texttt{))} |
| + | \end{matrix}</math> |
| |} | | |} |
| | | |
− | <math>\mathrm{E}g</math> tells you what you would have to do, from where you are in the universe <math>[u, v],\!</math> if you want to end up in a place where <math>g\!</math> is true. In this case, where the prevailing proposition <math>g\!</math> is <math>\texttt{((u, v))},</math> the component <math>\texttt{uv} \cdot \texttt{((du, dv))}</math> of <math>\mathrm{E}g</math> tells you this: If <math>u\!</math> and <math>v\!</math> are both true where you are, then change either both or neither of <math>u\!</math> and <math>v\!</math> at the same time, and you will attain a place where <math>\texttt{((du, dv))}</math> is true. | + | In general, <math>\mathrm{E}g\!</math> tells you what you would have to do, from wherever you are in the universe <math>[u, v],\!</math> if you want to end up in a place where <math>g\!</math> is true. In this case, where the prevailing proposition <math>g\!</math> is <math>\texttt{((} u \texttt{,~} v \texttt{))},\!</math> the component <math>uv \cdot \texttt{((} \mathrm{d}u \texttt{,~} \mathrm{d}v \texttt{))}\!</math> of <math>\mathrm{E}g\!</math> tells you this: If <math>u\!</math> and <math>v\!</math> are both true where you are, then change either both or neither of <math>u\!</math> and <math>v\!</math> at the same time, and you will attain a place where <math>\texttt{((} u \texttt{,~} v \texttt{))}\!</math> is true. |
| | | |
− | Figure 2.3 shows the expansion of <math>\mathrm{D}g</math> over <math>[u, v]\!</math> to produce the expression: | + | Figure 2.3 shows the expansion of <math>\mathrm{D}g\!</math> over <math>[u, v]\!</math> to produce the expression: |
| | | |
− | {| align="center" cellpadding="8" width="90%" | + | {| align="center" cellpadding="8" width="90%" |
− | | <math>\texttt{uv} \cdot \texttt{(du, dv)} ~+~ \texttt{u(v)} \cdot \texttt{(du, dv)} ~+~ \texttt{(u)v} \cdot \texttt{(du, dv)} ~+~ \texttt{(u)(v)} \cdot \texttt{(du, dv)}</math> | + | | |
| + | <math>\begin{matrix} |
| + | uv \cdot \texttt{(} \mathrm{d}u \texttt{,~} \mathrm{d}v \texttt{)} & + & |
| + | u \texttt{(} v \texttt{)} \cdot \texttt{(} \mathrm{d}u \texttt{,~} \mathrm{d}v \texttt{)} & + & |
| + | \texttt{(} u \texttt{)} v \cdot \texttt{(} \mathrm{d}u \texttt{,~} \mathrm{d}v \texttt{)} & + & |
| + | \texttt{(} u \texttt{)(} v \texttt{)} \cdot \texttt{(} \mathrm{d}u \texttt{,~} \mathrm{d}v \texttt{)} |
| + | \end{matrix}</math> |
| |} | | |} |
| | | |
− | <math>\mathrm{D}g</math> tells you what you would have to do, from where you are in the universe <math>[u, v],\!</math> if you want to bring about a change in the value of <math>g,\!</math> that is, if you want to get to a place where the value of <math>g\!</math> is different from what it is where you are. In the present case, where the ruling proposition <math>g\!</math> is <math>\texttt{((u, v))},</math> the term <math>\texttt{uv} \cdot \texttt{(du, dv)}</math> of <math>\mathrm{D}g</math> tells you this: If <math>u\!</math> and <math>v\!</math> are both true where you are, then you would have to change one or the other but not both <math>u\!</math> and <math>v\!</math> in order to reach a place where the value of <math>g\!</math> is different from what it is where you are. | + | In general, <math>\mathrm{D}g\!</math> tells you what you would have to do, from wherever you are in the universe <math>[u, v],\!</math> if you want to bring about a change in the value of <math>g,\!</math> that is, if you want to get to a place where the value of <math>g\!</math> is different from what it is where you are. In the present case, where the ruling proposition <math>g\!</math> is <math>\texttt{((} u \texttt{,~} v \texttt{))},\!</math> the term <math>uv \cdot \texttt{(} \mathrm{d}u \texttt{,~} \mathrm{d}v \texttt{)}\!</math> of <math>\mathrm{D}g\!</math> tells you this: If <math>u\!</math> and <math>v\!</math> are both true where you are, then you would have to change one or the other but not both <math>u\!</math> and <math>v\!</math> in order to reach a place where the value of <math>g\!</math> is different from what it is where you are. |
| | | |
− | Figure 2.4 approximates <math>\mathrm{D}g</math> by the linear form <math>\mathrm{d}g</math> that expands over <math>[u, v]\!</math> as follows: | + | Figure 2.4 approximates <math>\mathrm{D}g\!</math> by the linear form <math>{\mathrm{d}g}\!</math> that expands over <math>[u, v]\!</math> as follows: |
| | | |
| {| align="center" cellpadding="8" width="90%" | | {| align="center" cellpadding="8" width="90%" |
| | | | | |
− | <math>\begin{array}{lll} | + | <math>\begin{array}{*{9}{l}} |
| \mathrm{d}g | | \mathrm{d}g |
− | & = & \texttt{uv}\!\cdot\!\texttt{(du, dv)} + \texttt{u(v)}\!\cdot\!\texttt{(du, dv)} + \texttt{(u)v}\!\cdot\!\texttt{(du, dv)} + \texttt{(u)(v)}\!\cdot\!\texttt{(du, dv)} | + | & = & uv \cdot \texttt{(} \mathrm{d}u \texttt{,~} \mathrm{d}v \texttt{)} |
− | \\ \\ | + | & + & u \texttt{(} v \texttt{)} \cdot \texttt{(} \mathrm{d}u \texttt{,~} \mathrm{d}v \texttt{)} |
− | & = & \texttt{(du, dv)} | + | & + & \texttt{(} u \texttt{)} v \cdot \texttt{(} \mathrm{d}u \texttt{,~} \mathrm{d}v \texttt{)} |
| + | & + & \texttt{(} u \texttt{)(} v \texttt{)} \cdot \texttt{(} \mathrm{d}u \texttt{,~} \mathrm{d}v \texttt{)} |
| + | \\[8pt] |
| + | & = & \texttt{(} \mathrm{d}u \texttt{,~} \mathrm{d}v \texttt{)} |
| \end{array}</math> | | \end{array}</math> |
| |} | | |} |
| | | |
− | Figure 2.5 shows what remains of the difference map <math>\mathrm{D}g</math> when the first order linear contribution <math>\mathrm{d}g</math> is removed, namely: | + | Figure 2.5 shows what remains of the difference map <math>\mathrm{D}g\!</math> when the first order linear contribution <math>{\mathrm{d}g}\!</math> is removed, namely: |
| | | |
| {| align="center" cellpadding="8" width="90%" | | {| align="center" cellpadding="8" width="90%" |
| | | | | |
− | <math>\begin{matrix} | + | <math>\begin{array}{*{9}{l}} |
| \mathrm{r}g | | \mathrm{r}g |
− | & = & \texttt{uv} \cdot \texttt{0} & + & \texttt{u(v)} \cdot \texttt{0} & + & \texttt{(u)v} \cdot \texttt{0} & + & \texttt{(u)(v)} \cdot \texttt{0} | + | & = & uv \cdot 0 |
− | \\ \\ | + | & + & u \texttt{(} v \texttt{)} \cdot 0 |
− | & = & \texttt{0} | + | & + & \texttt{(} u \texttt{)} v \cdot 0 |
− | \end{matrix}</math> | + | & + & \texttt{(} u \texttt{)(} v \texttt{)} \cdot 0 |
| + | \\[8pt] |
| + | & = & 0 |
| + | \end{array}</math> |
| |} | | |} |
| | | |
Line 1,711: |
Line 1,732: |
| </pre> | | </pre> |
| |} | | |} |
− |
| |
− | <br>
| |
| | | |
| {| align="center" border="0" cellpadding="10" | | {| align="center" border="0" cellpadding="10" |
Line 1,757: |
Line 1,776: |
| </pre> | | </pre> |
| |} | | |} |
− |
| |
− | <br>
| |
| | | |
| {| align="center" border="0" cellpadding="10" | | {| align="center" border="0" cellpadding="10" |
Line 1,803: |
Line 1,820: |
| </pre> | | </pre> |
| |} | | |} |
− |
| |
− | <br>
| |
| | | |
| {| align="center" border="0" cellpadding="10" | | {| align="center" border="0" cellpadding="10" |
Line 1,849: |
Line 1,864: |
| </pre> | | </pre> |
| |} | | |} |
− |
| |
− | <br>
| |
| | | |
| {| align="center" border="0" cellpadding="10" | | {| align="center" border="0" cellpadding="10" |